ANALISIS DATA PENJUALAN TOKEH SAWIT DI INDRAGIRI HILIR MENGGUNAKAN POWER BI - wahyuni, tri (PT. ZIVANA CENDEKIAWAN BANGSA, 2025)
This research aims to analyze the oil palm tokeh business in Bumi Asih Hamlet, Karya Tunas Jaya Village, with a focus on three main aspects: the number of purchases of palm oil from farmers over two months, identification of the highest number of sales to palm fruit collectors, and comparison of the quantities between palm oil and loose fruit. The data collection method uses direct interviews with related parties, including farmers and fruit collectors. Data was analyzed using Power BI software for visualization of results. The main findings show that the highest palm oil purchases occurred in November, reaching 60,000 kg, with total purchases for two months amounting to 111,000 kg. Daily analysis shows a gradual increase with peak purchases on the 10th day, reaching 11,900 kg of palm oil. A comparison between palm oil and brondolan shows the dominance of palm oil at 89.4% (110,000 kg) compared to brondolan at 10.6% (13,000 kg). This research provides insight into the dynamics of the palm oil business and the potential for using information technology to increase efficiency and productivity in managing business processes.